Molecular‐Level Insights into the Notorious CO Poisoning of Platinum Catalyst. (23rd February 2022) - Chen, Wenyao; Cao, Junbo; Fu, Wenzhao; Zhang, Jing; Qian, Gang; Yang, Jia; Chen, De; Zhou, Xinggui; Yuan, Weikang; Duan, Xuezhi
Abstract: Carbon monoxide (CO) is notorious for its strong adsorption to poison platinum group metal catalysts in the chemical industry. Here, we conceptually distinguish and quantify the effects of the occupancy and energy of d electrons, emerging as the two vital factors in d‐band theory, for CO poisoning of Pt nanocatalysts. The stepwise defunctionalization of carbon support is adopted to fine‐tune the 5d electronic structure of supported Pt nanoparticles. Excluding other promotional mechanisms, the increase of Pt 5d band energy strengthens the competitive adsorption of hydrogen against CO for the preferential oxidation of CO, affording the scaling relationship between Pt 5d band energy and CO/H2 adsorption energy difference. The decrease of Pt 5d band occupancy lowers CO site coverage to promote its association with oxygen for the total oxidation of CO, giving the scaling relationship between Pt 5d occupancy and activation energy. The above insights outline a molecular‐level understanding of CO poisoning. Abstract : The occupancy and energy of metal d electrons are the two vital factors in d‐band theory. These factors have an effect on CO poisoning with distinct scaling relationships. An increase of Pt 5d band energy strengthens the competitive adsorption between CO and hydrogen, while a decrease of Pt 5d band occupancy lowers the site coverage of CO to promote its association with oxygen.